Assessment of Jeddah City Public Health Facilities Readiness to Combat Epidemics - Daghestani, Serajaddin Omar; Jamalallail, Faisal Mohammed (Journal of natural sciences, life and applied sciences, 2023)
The research aims to review the spatial analysis of health services and their readiness to combat and confront epidemics. It also aims to analyze the relationship between population density and the efficiency of the spread of government health services in the city. In the study, data and statistics issued by the Health Affairs in Makkah Al-Mukarramah region were used, relying on digital maps from the Municipality of the region and reports of the Statistics Authority. Then the data was processed in the ArcGIS map creation and analysis program. The research consists of an introduction, a problem presentation, and a review of the study data on maps. The results showed that the distribution of services extends north and south, and there is a dispersion in the distribution of health care centers and hospitals, most of which are located in the center. It became clear that more than 64% of the city is devoid of government health services at all levels, and it cannot meet the population’s needs for health services. It must develop and find new locations for health centers and hospitals to compensate for the shortfall.